Screening for Sarawak Paddy Landraces with Resistance to Yellow Rice Stem Borer, Scirpophaga incertulas (Walker) (Lepidoptera: Crambidae) - Xian, Alvin Rong Ling; Kuok, Freddy San Yeo; Nur Najwa, Hamsein; Hieng, Ming Ting; Mogeret, Sidi; Wan Nurainie, Wan Ismail; Annebell Stphanie, Taji; Yin, Hui Cheok (Universiti Putra Malaysia Pres, 2020)
The yellow rice stem borer, Scirpophaga incertulas (Walker) is a prevalent pestin paddy fields worldwide. In Sarawak, a survey on pest of paddy carried out from 2009 to 2011 covering 166 paddy fields revealed that rice stem borers caused 11.4% of total paddy damage. In order to reduce the damage, identifying resistance paddy variety is crucial. The objective of this study was to screen Sarawak paddy landraces with resistance toS. incertulas. Twelve Sarawak paddy landraces were selected randomly for this study. Antixenosis resistance screening was performed in aquariums (60 x 28 x 33 cm). Three replications of one-month-old seedlings were randomly arranged in aquarium and exposed to adult S. incertulas. The number and position of egg mass on each plant were recorded. Egg mass abnormalities were also observed. For antibiosis, rice culms of two-month old seedlings from each landrace were infested with larvae. The length of surviving larvae from five rice culms was measured. The experiment revealed variations in landrace of preference for ovipositing. Among the twelve Sarawak paddy landraces, Kanowit was more preferred by S. incertulas for ovipositing in comparison to other paddy landraces suggesting susceptibility towards the pest. Abaxial leaf surface was the preferred oviposition site. There was no clear antibiosis response of the paddy landraces towards S. incertulas larvae in this study.